Hubungan Antara BBLR, ASI Esklusif dengan Kejadian Stunting Pada Balita Usia 2-5 Tahun - Erna Eka Wijayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2019)
Stunting is a short toddler which is an indication of poor nutritional status and is used as a long-term indicator. The prevalence of stunting in Desa Jadi Subdistrict of Semanding in Tuban Regency, there are 144 children under five with 101 children (70%) experiencing stunting, 31 children (22%) experiencing short and 12 children (8%) normal. The purpose of this study was to determine the relationship between LBW, Exclusive breastfeeding and the incidence of stunting in infants aged 2-5 years in Jadi Subdistrict, Semanding District, Tuban Regency. This research uses analytic research with case control approach. The population of all mothers in the village So the Semanding sub-district who have toddlers aged 2-5 years by 85 respondents, a large sample of 85 respondents with total sampling techniques. Univariate and bivariate data analysis. The results showed that all toddlers with LBW all stunted as many as 28 respondents (100%) and toddlers who did not get exclusive breastfeeding almost all experienced stunting as many as 44 respondents (94%). By using the chi square test and calculated using SPSS version 21 with significance level α (0.05), the LBW is obtained with a stunting event p = 0,000 less than 0.05 and the relationship between ASI and the exclusive breastfeeding event p = 0,000 is smaller from 0.05. This shows that H1 is accepted which means there is a significant relationship between LBW, Exclusive breastfeeding and the incidence of stunting in children aged 2-5 years in Jadi Subdistrict, Semanding District, Tuban Regency. It can be concluded that the Birth Weight of a Baby and the giving of exclusive breastfeeding to a baby are very influential in the child's growth and development process.